2011
DOI: 10.1007/s10620-011-1614-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Colonoscope Training Model with the Colonoscope 3D Imaging Probe Improved Trainee Colonoscopy Performance: A Pilot Study

Abstract: Colonoscopy simulation using the Colonoscope Training Model and the ScopeGuide produced an immediate and large effect on trainee colonoscopy performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…This is why colonic tattooing is necessary to mark a colonic lesion before laparoscopic resection. The use of magnetic imaging such as with Olympus ScopeGuide™, coMputed toMography findings of Bowel wall thicKening: its significance and relationship to endoscopic aBnorMalities UzzAMAN ALAM NAIR BORGSTEIN MELEAGROS which would give an accurate anatomical location of a lesion, 18,19 would have been useful to clarify the accuracy of endoscopic evaluation in locating lesions in this study. Rockey et al 2 and Padda et al 12 suggested that patients who have high clinical suspicion for GI pathology but a negative endoscopy should have a double contrast barium enema or repeat CT with emphasis on optimal luminal distension.…”
mentioning
confidence: 99%
“…This is why colonic tattooing is necessary to mark a colonic lesion before laparoscopic resection. The use of magnetic imaging such as with Olympus ScopeGuide™, coMputed toMography findings of Bowel wall thicKening: its significance and relationship to endoscopic aBnorMalities UzzAMAN ALAM NAIR BORGSTEIN MELEAGROS which would give an accurate anatomical location of a lesion, 18,19 would have been useful to clarify the accuracy of endoscopic evaluation in locating lesions in this study. Rockey et al 2 and Padda et al 12 suggested that patients who have high clinical suspicion for GI pathology but a negative endoscopy should have a double contrast barium enema or repeat CT with emphasis on optimal luminal distension.…”
mentioning
confidence: 99%
“…In addition the need for assistance with the procedure from a senior colleague was significantly less in the group utilising MEI (19% v 40%, p=0.02). This may lead to the conclusion that the benefit of the device may be more of a training tool for trainee endoscopists through identification of loops, as shown by similar performance improvements in this group in other cohort studies [12][13][14].…”
Section: Mei Use In Clinical Practicementioning
confidence: 63%
“…Despite these promising findings, studies that have evaluated the use of the Kyoto Kagaku model as a training tool (rather than an assessment tool) have produced mixed results 9 24. One recent study found that surgical residents who engaged in unstructured training using the model showed no improvement in their Global Assessment of Gastrointestinal Endoscopic Skills scores from pretest to posttest 9.…”
Section: Introductionmentioning
confidence: 99%